Clinical Outcomes of Older Patients with Non-Variceal Upper Gastrointestinal Bleeding Taking Anti-Thrombotic or Non-Steroidal Anti-Inflammatory Agents - Durak, Muhammed Bahaddin; Şimşek, Cem; Yüksel, İlhami (Turkish Journal of Gastroenterology, 2023)
Background/Aims: Non-variceal upper gastrointestinal bleeding is a well-established complication of non-steroidal anti-inflammatory drugs and anti-thrombotics. Both medication groups are frequently used by older populations and increase the incidence of non-var- iceal upper gastrointestinal bleeding; however, their impact on etiology and outcomes of non-variceal upper gastrointestinal bleeding has not been well defined. We aimed to compare the etiology and outcomes of non-variceal upper gastrointestinal bleeding in older patients who use anti-thrombotics and non-steroidal anti-inflammatory drugs or do not use either of them. Materials and Methods: This is a single-center prospective study of patients older than 65 years with non-variceal upper gastrointesti- nal bleeding. Endoscopic findings, laboratory values, blood transfusion, endoscopic treatment, re-bleeding, and 30-day mortality rates were recorded. Results: A total of 257 patients (median age 77.7 ± 8.2, 59% male) were included. Re-bleeding occurred in 25 (10%) and the 30-day mortality rate was 40 (16%). There was no statistically significant difference between patients using anti-thrombotics, non-steroidal anti-inflammatory drugs or non-users for blood transfusion (P = .46), endoscopic hemostasis (P = .39), re-bleeding (P = .09), and 30-day mortality (P = .45). Peptic ulcer was the most common etiology in all groups (124, 48%). Although the incidence of peptic ulcer was similar between drug users and anti-thrombotic users (P = .75), the incidence of peptic ulcer was significantly higher in patients using non-steroidal anti-inflammatory drugs than in patients who did not use drugs (P = .05). When the patients were analyzed as using anti- thrombotic drugs or non-steroidal anti-inflammatory drugs or neither, no statistically significant difference was found between ulcer location, ulcer number, and ulcer size. Conclusion: Non-variceal upper gastrointestinal bleeding increasingly occurs in older populations with several comorbidities; non- steroidal anti-inflammatory drugs or anti-thrombotics do not seem to change the clinical outcomes among older patients with non- variceal upper gastrointestinal bleeding.